2023
DOI: 10.1371/journal.pone.0278728
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characterization and factors associated with quality of life in Long COVID patients: Secondary data analysis from a randomized clinical trial

Abstract: Background Long COVID patients suffer a negative impact on their quality of life, as well as their functioning, productivity or socialization. There is a need to better understand the individual experience and circumstances surrounding these patients. Objective To characterize clinical picture of Long COVID patients and to identify factors associated with quality of life. Methods A secondary data analysis from a randomized clinical trial (RCT) was carried out with 100 Long COVID patients treated by Primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…On the one hand, this may be explained by the fact that the DSQ-PEM has not been validated specifically for high-performance athletes after COVID-19 infection. On the other hand, other cognitive and emotional aspects in athletes may play a role; it has been shown that long-COVID-19 syndrome is associated with a decrease in mental health and reduced quality of sleep [ 41 ]. Patients without measurable CPET limitations and pathological DSQ-PEM scores could benefit from neuro-meditation programs, as these have been shown to improve mental health, depression, and anxiety in PASC [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, this may be explained by the fact that the DSQ-PEM has not been validated specifically for high-performance athletes after COVID-19 infection. On the other hand, other cognitive and emotional aspects in athletes may play a role; it has been shown that long-COVID-19 syndrome is associated with a decrease in mental health and reduced quality of sleep [ 41 ]. Patients without measurable CPET limitations and pathological DSQ-PEM scores could benefit from neuro-meditation programs, as these have been shown to improve mental health, depression, and anxiety in PASC [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long COVID is still considered a new and unknown disease, 63 and treatment options remain limited, [4][5][6] leading patients suffering from this disease to feel frustrated when seeking treatment, willing to try anything to control and manage their symptoms and recover their highly deteriorated quality of life. 64,65 This could explain the high levels of motivation at the beginning of our study.…”
mentioning
confidence: 82%
“…This was a cross-sectional study analyzing data from the baseline assessment of a randomized clinical trial entitled "Analysis of the symptoms and quality of life of people with a diagnosis of long COVID-19, and the effectiveness of an intervention in primary care using ICTs" (reference number ISRCTN91104012) [22][23][24].…”
Section: Methodsmentioning
confidence: 99%